Empowering Voices: A Three-Year Intervention to Reduce Public Speaking Anxiety among ESL Learners - Pontillas, Marlon S. (Journal of Social and Scientific Education, 2025)
This paper outlines a structured, research-based intervention program designed to reduce public speaking anxiety among ESL learners at Camarines Sur Polytechnic Colleges and its partner, Zeferino Arroyo High School. Spanning three years, the program consists of three progressive phases: "Speak Up!" (2022), "Speak Out!" (2023), and "Speak Your Voice!" (2024). Based on the Popsispeak framework, these intervention activities integrate impromptu speaking exercises, peer collaboration, and ongoing feedback to build public speaking skills, enhance confidence, and decrease anxiety. The program’s objectives include enhancing participants' knowledge of public speaking principles, fostering a supportive learning environment that promotes positive attitudes, and developing articulation, fluency, and effective delivery skills, as outlined in public speaking literature. Evaluative data reveal substantial improvements across these domains, with notable reductions in speaking anxiety and gains in confidence and skill. This intervention aligns with Sustainable Development Goal 4, promoting inclusive and quality education, and addresses regional employability concerns by enhancing English proficiency. Recommendations for future implementation emphasize extending session durations, incorporating more real-world communication tasks, and maintaining a non-judgmental environment to support continuous improvement. The success of the Popsispeak framework suggests that similar structured, experiential interventions could enhance communication skills across educational and professional contexts.